Group Guidance with Gestalt Support Based on Ukhuwah Islamiyah in Madrasah Aliyah, UIN Laboratory, North Sumatra, Medan - Siahaan, Dina Nadira Amelia; Zunidar, Zunidar (Universitas Islam Negeri Raden Intan Lampung, 2020)
Ukhuwah Islamiyah is an equivalent term for good social interaction between individuals in Islam. The concept of ukhuwah or brotherhood can be realized through guidance and counseling efforts. In the